2006
DOI: 10.1038/nature05175
|View full text |Cite
|
Sign up to set email alerts
|

Molecular architecture and assembly of the DDB1–CUL4A ubiquitin ligase machinery

Abstract: Protein ubiquitination is a common form of post-translational modification that regulates a broad spectrum of protein substrates in diverse cellular pathways. Through a three-enzyme (E1-E2-E3) cascade, the attachment of ubiquitin to proteins is catalysed by the E3 ubiquitin ligase, which is best represented by the superfamily of the cullin-RING complexes. Conserved from yeast to human, the DDB1-CUL4-ROC1 complex is a recently identified cullin-RING ubiquitin ligase, which regulates DNA repair, DNA replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
703
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(731 citation statements)
references
References 26 publications
27
703
1
Order By: Relevance
“…CPSF-160 also bears weak sequence homology with the ubiquitin ligase DDB1, for which structural information has been obtained [97,98]. DDB1 contains three β-propellers (each with 7 repeats) and a C-terminal domain.…”
Section: Cpsf-160 (Cft1p/yhh1p)mentioning
confidence: 99%
“…CPSF-160 also bears weak sequence homology with the ubiquitin ligase DDB1, for which structural information has been obtained [97,98]. DDB1 contains three β-propellers (each with 7 repeats) and a C-terminal domain.…”
Section: Cpsf-160 (Cft1p/yhh1p)mentioning
confidence: 99%
“…Mass spectrometry analysis revealed these proteins as DDB1 and VprBP, respectively (Figure 1a). VprBP and DDB1 have been shown to assemble with Cul4A and Roc1 to form an E3 ubiquitin ligase complex (Angers et al, 2006;He et al, 2006;Higa et al, 2006;Jin et al, 2006b). In addition, several peptides derived from DDA1, an additional component of the Cul4A ligase complex, were also identified from the purification (Table 1).…”
Section: Identification Of Vprbp and Ddb1 As Merlin-associated Proteinsmentioning
confidence: 99%
“…The Cullin E3 ligases have been shown to target a number of proteins for ubiquitination-dependent proteolysis via different adaptor proteins that afford specific substrate recognition (Higa and Zhang, 2007;Lee and Zhou, 2007). Recently, multiple WD40 domain-containing proteins were found to interact with DDB1 and serve as the substrate-recognition subunits of the CUL4-DDB1 ubiquitin ligase complex (Angers et al, 2006;He et al, 2006;Higa et al, 2006;Jin et al, 2006b). One of these WD40 domain-containing proteins, VprBP/ DCAF1, contains four WD40 domains and a LisH domain.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these data suggest that the cell cycle defects that we have observed in undamaged, DTL-depleted cells are entirely caused by the deregulation of CDT1. Contemporaneous with our study, others have shown that DTL/CDT2 is one of several DDB1-and CUL4-associated factors (DCAFs) and that DTL/CDT2 is required for CDT1 degradation (Angers et al 2006;Higa et al 2006;Jin et al 2006). …”
Section: A Critical Role For Dtl In Preventing Rereplication Through mentioning
confidence: 99%